Integration Of Anesthesia Into ECT: A Hospital- Based Study On MECT From Anesthesiologist Point Of View - Neupane, S; Pahari, T; Lamichhane, N; Thapa, DK (Journal of Psychiatrists' Association of Nepal, 2020)
Introduction: MECT is a unique procedure where psychiatrist and anesthesiologist work together as a team. It is estimated that annually, approximately 1 million patients receive ECT worldwide. Due to association of physical complications like long bone and vertebrae fractures with direct ECT, anesthesia has been integrated into ECT. MECT is now the globally accepted standard mode of ECT. This study was done to see the Socio-demographic and clinical profile of patients receiving MECT. Material And Method: This is a hospital-based study done in BG hospital and Research Centre, Pokhara, Nepal for the duration of 12 months; from Baisakh, 2074 to Chaitra, 2074. A total of 50 consecutives cases that received MECT were enrolled after written informed consent for the ECT from the patients’ caretaker. The patient’s details, diagnosis and the numbers of cycles of MECT thus applied till clinical improvement were noted during the study period. MECT was administered on alternate days. The assessment of clinical improvement was done by the consultant psychiatrist. Following the protocol, each cycle of MECT was applied by consultant psychiatrist in the presence of the consultant anesthesiologist. Results: The total number of cases enrolled were 50. Out of 50 cases, 41 (82%) were male and mean age was 30.60 ± 10.13 years. The most common indications for MECT were BPAD (74%). The number of cycles of modified MECT applied on the individuals ranged from 6 to 18 cycles. Majority of the cases (78%) seem to have a clinical improvement after 6 cycles of modified ECT. There was no complication that warranted the termination of MECT. Conclusion: MECT when used judiciously is safe and leads to better clinical improvement.